The Mutagenesis of Lactobacillus Thermophilus for Enhanced L-(+)-Lactic Acid Accumulation Induced by Heavy Ion Irradiation - Hu,Wei (2017)
ABSTRACT Screening promising L. thermophiles with high productivity, high efficiency and strong adaptability are very important in lactic acid industry. For this purpose, 80MeV/u carbon ions were applied to irradiate L. thermophiles. After high-throughput screening, a mutant, named SRZ50, was obtained. Different carbon sources or nitrogen sources were provided to investigate carbon or nitrogen source utilization between mutant SRZ50 and wild type, and different fermentation periods were also chose to study fermentation characteristic between mutant SRZ50 and wild type. The results showed that mutant SRZ50 exhibited the enhanced L-(+)-lactic acid production from wild type. When glucose or fructose was the sole carbon source, the L(+)-lactic acid production by mutant SRZ50 was both the highest, respectively, 23.16 ± 0.72 g/L or 23.24 ± 0.66 g/L, which had a significant increase from that of wild type (P<0.01), following obvious increase in biomass (P<0.05). When yeast powder was the sole nitrogen source, it can promote mutant SRZ50 to accumulate the highest L-(+)-lactic acid accumulation, which also had a significant increase from that of wild type (P<0.01). Under different fermentation periods, it was obtained that mutant SRZ50 all exhibited significant increase in L-(+)-lactic acid accumulation from wild type. In conclusion, a mutant strain with improved production profiles for L-(+)-lactic acid, was obtained, indicating that heavy ions can be an efficient tool to improve metabolic product accumulations in microbes.